Characterization of group III-nitride nanowires for bio-electrochemical sensors - Wallys, Jens Matthias Emil; Justus Liebig University Giessen (My University, 2014)
In the present work, the potential of group III-nitride nanowire (NW) ensembles for application as bio-chemical sensors with optical readout was evaluated. The sample analysis was divided into two main parts. At first, an electrochemical analysis with impedance spectroscopy and cyclic voltammetry was conducted. The second part comprises a photoelectrochemical examination by means of photoluminescence spectroscopy at room temperature.In the electrochemical characterization by impedance spectroscopy the recorded impedance spectra were evaluated by comparison to an electrical equivalent circuit. The influence of Silicon- and Magnesium-doping on the extracted parameters defining the NW/electrolyte interface, the surface capacitance (CS) and the surface resistance (RS), was investigated. Comparing the n.i.d. GaN NW ensembles to Si-doped ensembles reveals an increase of CS with a simultaneous reduction of RS. This is assigned to the formation of a conductive channel inside the NWs. For Mg-doped NWs only a slight increase of RS in combination with a small decrease of CS was observed and assigned to compensation of the residual n-type doping.According to the extracted electrochemical parameters the NWs were classified into two groups. On the one hand, the conductive NWs, defined by a highCS in combination with a low RS. On the other hand, the resistive NWs which were characterized by a lower CS and higher RS. The differences between these two groups were explained in terms of different bandprofiles within the NWs. Assuming a constant diameter along the NW growth axis the width of the space charge region depends on the doping concentration. Due to Si-diffusion the doping concentration is known to be higher in the region close to the interface to the Si substrate. The interplay between the NW diameter and the surface band bending (SBB) determines the potential barrier Ufb for electrons to reach the surface. For conductive NW a high doping concentration and/or a large diameter allows the formation of a conductive channel in the NW so that the complete NW to contributes to CS and RS. On the contrary, a resistive NW with a thin diameter is fully depleted of charge carriers as the space charge region is extended throughout the whole NW. This model was approved by cyclic voltammetry measurements which indicate the interfacial charge transfer into a redox couple ccurring only for conductive NWs. Bias application allows for the modification of the SBB inside the NWs which was investigated by bias-dependent IS analysis. Cathodic bias application decreases the space charge region for resistive NWs, resulting in an increase of CS accompanied by a significant decrease of RS. Anodic bias application showed the opposite effect of a sharply increased RS and a slightly decreased CS for the conductive NW sample with the highest Si-concentration, indicating that the electrical characteristics of NWs can be controlled by externally applied bias.The photoluminescence of GaN NW ensembles in electrolyte solution was characterized as a function of the externally applied bias (UC) and the pH value. It was shown that the intensity of the PL intensity strongly depends on the bias and the pH, while its energetic position and full width at half maximum (FWHM) remain unchanged. These results were discussed on the basis of the extended "dead layer" model for semiconductors, assuming the absence of radiative recombination within the space charge region. Photo-generated charge carriers can either recombine non-radiatively at the surface or radiatively in the field-free NW center. The application of cathodic bias at constant pH directly impacts the SBB with the result that photo-generated holes are no longer attracted towards the surface. As a consequence the radiative recombination rate increases while non-radiative losses at the surface decrease. At constant bias the decrease of the pH value below 7 leads to a similar increase of the intensity. This was explained in terms of the site-binding model which states that in acidic solutions the surface becomes more positively charged. This impacts the SBB in a similar manner as cathodic bias. The "extended dead layer model" was confirmed by analysis of Si-doped NWs that exhibit a higher SBB due to the smaller width of the SCR. First results on the influence of Mg-doping of GaN NWs were presented.Finally, a conceptional study of NW ensembles as an optical transducer for pH detection was briefly presented. The data indicated that with the setup used here a pH resolution of 0.05 pH can be achieved with high reproducibility. Additionally, two proof of principle measurements were presented where the enzymatically catalyzed production of penicilloic acid accompanied by a subsequent pH change was optically detected with GaN and InGaN/GaN NWs.

Thema der vorliegenden Arbeit ist die Charakterisierung von Gruppe III-Nitrid Nanostrukturen für eine mögliche Anwendung als nanophotonische Sonden in der biochemischen Sensorik. Die elektrochemische Charakterisierung der NW wurde mittels Impedanzspektroskopie und zyklischer Voltammetrie durchgeführt. Die Extraktion der elektrochemischen Grenzflächenparameter Oberflächenwiderstand (RS) und Oberflächenkapazität (CS) wurde durch den Vergleich mit elektrischen Ersatzschaltbildern möglich. In einem weiteren Schritt wurden die n.i.d. NW mit NW, die mit Silizium bzw. Magnesium dotiert waren, verglichen. Dabei zeigte sich, dass die Dotierung mit Silizium eine Erhöhung von CS bewirkt, während der Wert für RS kontinuierlich absinkt. Die Dotierung mit Magnesium führte lediglich zu einer geringen Erhöhung des Oberflächenwiderstands kombiniert mit einer minimalen Verringerung der Oberflächenkapazität. Aus dem beobachteten Verhalten konnte der Übergang zur vollständigen p-typ Leitung im ND ausgeschlossen werden. Messungen der offenen Klemmspannung hingegen zeigten, dass es vor allem bei NW mit hoher Magnesium- Konzentration zur Ausbildung von Bereichen kommt, die p-typ charakteristisches Verhalten aufweisen. Eine Unterteilung der NW gemäß ihrer elektrochemischen Parameter erfolgt in zwei Gruppen: Die erste Gruppe, als "conductive" bezeichnet, zeichnet sich durch einen großen Wert CS und einen niedrigen Wert RS aus. Die zweite Gruppe, welche als "resistive" bezeichnet wird, wird repräsentiert von erniedrigten Werten für CS und erhöhten Werten für RS. Physikalisch bedeutet dies, dass dieNWder "resitive" Gruppe komplett von freien Ladungsträgern verarmt sind. Die von den Oberflächenzuständen hervorgerufene Raumladungszone schließt in diesem Fall das komplette Drahtvolumen ein. In NWs der Gruppe "conductive" findet sich im Zentrum ein Bereich, in dem Leitungs- und Valenzband ihr Bulkniveau erreichen. Dieser Bereich (leitender Kanal) ist feldfrei und bewirkt, dass größere Volumina des NW zur Bildung der Oberflächenkapazität beitragen. Dieser Effekt kann entweder durch eine Erhöhung der n-Typ Dotierung oder durch eine Vergrößerung des NW-Durchmessers erreicht werden. In beiden Gruppen von NW ist zudem aufgrund der inhomogenen Dotierkonzentration und der lateralen Aufweitung der Drähte von einem sich axial verändernden Bandprofil auszugehen. Das präsentierte Modell wurde durch die Messung des Ladungstransfers in das Redoxpaar mittel zyklischer Voltammetrie, welcher nur bei NW aus der Gruppe "conductive" beobachtet werden konnte, unterstützt. Eine weitere Bestätigung der Bandprofilinterpretation wurde durch Anlegen einer externen Spannung und deren Einfluss auf die elektrochemischen Parameter erreicht.An der NW Probe mit der höchsten Silizium-Konzentration konnte bei Anlegen einer anodischen Spannung der umgekehrte Effekt, nämlich eine Verringerung von CS und einer Erhöhung von RS, gezeigt werden. Des Weiteren wurde die Photolumineszenz der Nanodrähte im Elektrolyten bei Raumtemperatur untersucht. Dabei zeigte sich, dass die Intensität der von den NW herrührenden PL auf extern angelegte Spannungen und den pH-Wert des Elektrolyten reagiert, wobei die energetische Position und die Halbwertsbreite (FWHM) konstant blieben. Eine Erhöhung des an den NW vorliegenden Potenzials in kathodischer Polarität führte zu einer Erhöhung der PL-Intensität bei konstantem pH. Durch das Absenken des pH Wertes in den sauren Bereich bei konstant gehaltener Spannung wurde ebenfalls eine Erhöhung der Intensität erreicht. Die Spannungs- und pH-Abhängigkeit der PL-Intensität wurde auf Grundlage des in der Literatur bekannten "Dead Layer Models" für Schichten beschrieben. Dabei wurde die PL-Intensität als Verhältnis zwischen strahlender Rekombination im Bulk und nicht strahlender Rekombination an der Oberfläche bezeichnet. Das Anlegen einer kathodischen Spannung führt zu einer Verringerung der Oberflächenbandverbiegung und erhöht damit die strahlende Rekombinationsrate. Um das Modell an die veränderten Bedingungen bei den im Rahmen dieser Arbeit untersuchten NW anzupassen, wurde eine sich entlang der NW Wachstumsachse verändernde Oberflächenbandverbiegung in Form einer sich exponentiell verringernden Flachbandspannung Ufb, berücksichtigt.Aufbauend auf den Ergebnissen zur pH-abhängigen PL-Intensität von GaN NW wird in dieser Arbeit ein mögliches Sensorkonzept vorgestellt. Hierzu wurde aus den Spannungs- und pH-abhängigen Messungen eine optische Transkonduktanz ermittelt, welche die Definition eines Sensorarbeitspunktes in Abhängigkeit des zu erwartenden pH-Intervalls erlaubt.In zwei die prinzipielle Funktion prüfenden Untersuchungen "proof of principle" wird die Detektion einer pH-Änderung, hervorgerufen durch enzymatisch umgewandeltes Penicillin-G in Penicillinsäure und deren anschließende Dissoziation, mittels GaN und InGaN/GaN NW vorgestellt.
Charakterisierung von Gruppe III-Nitirid Nanodrähten für bioelektrochemische Sensoren
Keywords: Nanodrähte; GaN; pH; Lumineszenz; Elektrochemie; nanowire; GaN; pH; luminescence; electrochemistry; ddc:530